A new quinoxaline-containing peptide induces apoptosis in cancer cells by autophagy modulation1. Issue 8 (14th August 2015) - Zamudio-Vázquez, Rubí; Ivanova, Saška; Moreno, Miguel; Hernandez-Alvarez, Maria Isabel; Giralt, Ernest; Bidon-Chanal, Axel; Zorzano, Antonio; Albericio, Fernando; Tulla-Puche, Judit
<x xml:space="preserve">Abstract</x> The most cytotoxic compound from a library of quinoxaline-containing peptides is endocyted into HeLa cells, accumulates in acidic compartments, and blocks autophagy by altering lysosomal function, leading to apoptosis activation.